Cover Feature: Controlling the Formation of Sodium/Black Phosphorus IntercalationCompounds Towards High Sodium Content (8/2021). Issue 8 (19th July 2021) - Werbach, Katharina; Neiss, Christian; Müllner, Alexander; Abellán, Gonzalo; Setman, Daria; Lloret, Vicent; Wild, Stefan; Hauke, Frank; Pichler, Thomas; Hirsch, Andreas; Peterlik, Herwig
Abstract : The Cover Feature shows the structure of a stage 2 sodium‐black phosphorus intercalated compound (Na‐BPIC) in front of its X‐ray diffraction pattern that has been instrumental for its determination. The compound was successfully synthesized without containing intermetallic phases from pure black phosphorus (in the background) and pure sodium via ball‐milling. The image was designed by Rafal Konkol at the Universität Wien graphics department. More information can be found in the Communication by K. Werbach and co‐workers .